Influência do sexo nas diferenças comportamentais promovidas pela exposição ao etanol em peixes-zebra submetidos à interação com um objeto não familiar - Souza, Thiele Piber de (2021)
In humans, ethanol (EtOH) modulates behavioral functions in a biphasic manner, ranging from disinhibition to sedation. The effects of EtOH are dose-dependent and influenced by environmental and individual factors, such as the biological sex. The use of animal models represents a promising tool to assess whether EtOH modulates different behavioral domains in a sex-dependent manner. The zebrafish (Danio rerio) has the main neurotransmitter systems involved in EtOH-mediated responses and, due to its high pharmacological sensitivity, represents an attractive model system to assess the behavioral effects of EtOH on brain functions. Thus, we investigated whether the acute effects of different EtOH concentrations are sex-dependent in zebrafish submitted to the open field test (OFT) with the influence of a non-familiar object. Animals were separated by sex into four groups and acutely exposed to EtOH (0%, 0.25%, 0.5% and 1.0% v/v) for 1 h. After exposure, fish were individually placed into the OFT, which contained a non-familiar object (black sphere; diameter: 1 cm) fixed in the central area of the apparatus. Behavioral activity was recorded for 5 min. For the behavioral analysis, the tank was virtually divided into three areas: peripheral, intermediate and central. At the baseline, females showed a distinct exploratory activity and interaction pattern with the object, reflecting a more anxious and shy behavior in relation to males. Females exposed to 0.5% EtOH showed increased faster investigation to the object when compared to males, while exposure to 1.0% EtOH reduced locomotion in both sexes and increased immobility only in males. Principal component analysis (PCA) revealed that the components that most represented total variances of behaviors were anxiety-like responses, exploratory activity, and locomotion. Collectively, our new findings show the existence of a sex-dependent effect in zebrafish models acutely exposed to EtOH tested in the OFT with a non-familiar object. Thus, the present study encourages the use of the zebrafish models of EtOH exposure to assess how sex influences distinct behavioral phenotypes in future translational neuroscience research.